Development of Augmented Reality-Integrated Booklets and Flash Cards to Enhance Students’ Scientific Literacy and Motivation on Biodiversity Topics at SMA Negeri 2 Marang Kayu - Umi Khusna; Makrina Tindangen; Sonja Verra Tinneka Lumowa; Taufan Purwokusumaning Daru; Muhammad Amir Masruhim; Sukartiningsih (Jurnal Penelitian Pendidikan IPA, 2026)
This study was motivated by the low levels of students’ scientific literacy and learning motivation in biodiversity topics, as well as the limited availability of learning media capable of visualizing abstract concepts contextually at SMA Negeri 2 Marang Kayu. This study aimed to describe the validity, practicality, and effectiveness of Augmented Reality (AR)-integrated Booklet and Flash Card media in improving students’ scientific literacy and learning motivation. The study employed a Research and Development (R&D) method using the 4D model, which consists of define, design, develop, and disseminate stages. The research subjects included material experts, media experts, language experts, and tenth-grade students of SMA Negeri 2 Marang Kayu as the trial participants. The research instruments consisted of validation sheets, student response questionnaires, scientific literacy tests, and learning motivation questionnaires. The data were analyzed descriptively, while the effectiveness of the media was tested using a paired sample t-test and N-gain score analysis. The results showed that the developed media were categorized as highly valid, with validation scores of 96% from language experts, 90% from material experts, and 87% from media experts. The media were also considered highly practical based on students’ responses. Furthermore, the media proved to be significantly effective (p < 0.05) in improving students’ scientific literacy and learning motivation. Students’ scientific literacy scores increased from 57.63 to 79.63, while learning motivation scores increased from 61.05 to 75.59.